2018
DOI: 10.5194/isprs-archives-xlii-3-1499-2018
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Capabilities of Sentinel-2 for Vegetation Mapping Using Random Forest

Abstract: ABSTRACT:Accurate vegetation mapping is essential for monitoring crop and sustainable agricultural practice. This study aims to explore the capabilities of Sentinel-2 data over Landsat-8 Operational Land Imager (OLI) data for vegetation mapping. Two combination of Sentinel-2 dataset have been considered, first combination is 4-band dataset at 10m resolution which consists of NIR, R, G and B bands, while second combination is generated by stacking 4 bands having 10m resolution along with other six sharpened ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The authors mapped two forest types (evergreen and moist semi-deciduous forest) in south Ghana applying the SVM method to Sentinel-2 and hyperspectral data and achieved an overall accuracy of 92%. A study by Saini et al [33] demonstrated the superiority of the Sentinel-2 data over the Landsat-8 data in vegetation type classification in India. They tested both datasets for mapping vegetation types including wheat, fodder, trees, fallow land sugarcane, water, other crops built up and sandy area using the RF approach.…”
Section: Discussionmentioning
confidence: 99%
“…The authors mapped two forest types (evergreen and moist semi-deciduous forest) in south Ghana applying the SVM method to Sentinel-2 and hyperspectral data and achieved an overall accuracy of 92%. A study by Saini et al [33] demonstrated the superiority of the Sentinel-2 data over the Landsat-8 data in vegetation type classification in India. They tested both datasets for mapping vegetation types including wheat, fodder, trees, fallow land sugarcane, water, other crops built up and sandy area using the RF approach.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the availability and accessibility of remote sensing data, a huge variety of applications like crop type classification, vegetation mapping, forestry, precision agriculture, landslide susceptibility mapping, built up extraction, etc. have attracted the attention of multidisciplinary researchers [1][2][3][4][5][6][7][8]. Vegetation mapping is one of the essential application needs which has to be addressed effectively for overall environmental monitoring [8].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation mapping is one of the essential application needs which has to be addressed effectively for overall environmental monitoring [8]. The utilization of remotely sensed data is the optimal way for vegetation mapping because of the free availability of medium and coarser spatial resolution data, having different spatial and spectral properties, cost effective and less time consuming in comparison to traditional field survey methods [7,8]. Quantifying vegetation provides a valuable information for socio-economic applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations